First year university students’ use of formulaic sequences in oral and written descriptions (2015)
The present article investigates the use of first year university students’ formulaic sequences in written and oral texts in an English as a foreign language context. The corpus of the study consists of eight descriptive texts—four written and four oral—which were composed of four students of English Pedagogy at a university in Santiago, Chile. The investigation is a case study where the corpora were analysed qualitatively. The results show that first-year students use similar formulaic sequences in written and oral texts and many of the expressions generally used in spoken discourse are used by students in written texts.Este artículo presenta el uso de secuencias formulaicas de estudiantes universitarios de primer año en textos orales y escritos. El corpus del estudio está formado de ocho textos descriptivos, de los cuales cuatro son textos escritos y cuatro son textos orales. Los textos fueron desarrollados por cuatro estudiantes de pedagogía en inglés de una universidad en Santiago de Chile. La investigación es un estudio de caso, y el análisis de datos es cualitativo. Los resultados muestran que los estudiantes usan secuencias formulaicas idénticas tanto en el discurso oral como escrito, y muchas de las expresiones utilizadas en el discurso escrito son particulares del discurso oral del género de descripción.